Pyroptosis in Kawasaki disease: from mechanisms to targeted interventions - Han, Xiang-Yu; Qi, Hui-Ru (Frontiers in Immunology, 2025)
Kawasaki disease (KD) is a relatively common autoimmune disease of childhood, characterized by systemic vasculitis and involvement of the cardiovascular system, particularly the coronary artery. Progressive inflammatory cascades and vascular injury are regarded as two major processes underlying KD. Although it is regarded as a self-limiting disease, some children exhibit resistance to intravenous immunoglobulin (IVIG) treatment, which can lead to the development of life-threatening coronary artery aneurysms that persist into adulthood. Pyroptosis, a special inflammatory cell death pattern, results in the intense release of inflammatory mediators and injuries of tissues such as endothelial cell damage. Evidence from in vitro studies and animal models suggests that pyroptosis and associated inflammatory cascades may play a significant role in KD. Here, we highlight the latest insights into pyroptosis in KD and explore the potential therapeutic interventions that target pyroptosis.